The diagnostic value of serum 25-Hydroxyvitamin D, MIS and Insulin-like Growth Factor 1 for polycystic ovary syndrome (PCOS): Serum 25-Hydroxyvitamin D, MIS and Insulin-like Growth Factor 1 for polycystic ovary syndrome (PCOS) - Sun, Shaomeng; Zheng, Jianrui; Xie, Ziying (Journal of Medical Biochemistry, 2025)
Objective To investigate blood levels and the importance of Müllerian Inhibiting Substance (MIS), insulin-like growth factor 1 (IGF-1), insulin-like growth factor binding protein 3 (IGFBP-3), and 25-hydroxyvitamin D [25(OH)D] in patients with polycystic ovarian syndrome (PCOS).Methods The observation group consisted of 212 PCOS patients who received treatment at this institution between May 2022 and May 2024, while the control group consisted of 212 healthy women who were examined physically at same hospital within the same time frame. The two groups' general information, serum 25(OH)D, MIS, IGF-1, and IGFBP-3 levels, as well as their sex hormones and glucose metabolism markers, were compared. PCOS patients were divided into the IR group and the non-IR group according to whether insulin resistance (IR) occurred. The two groups' levels of serum 25(OH)D, MIS, IGF-1, and IGFBP-3 were compared. The study examined the associations among the four markers and the homeostasis model of insulin resistance index (HOMA-IR), as well as their supplementary diagnostic utility for PCOS.Results The level of 25(OH)D in the observation group was lower than that in the control group (P
Keywords: Polycystic ovary syndrome; 25-hydroxyvitamin D; Insulin-like growth factor 1; Insulin-like growth factor binding protein 3; Anti-Mullerian hormone